2013
DOI: 10.7326/0003-4819-159-11-201312030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon-α2a With or Without Low-Dose Ribavirin for Treatment-Naive Patients With Hepatitis C Virus Genotype 1 Receiving Hemodialysis

Abstract: National Center of Excellence for Clinical Trial and Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 42 publications
1
82
1
2
Order By: Relevance
“…Despite the fact that ribavirin is contraindicated in the setting of renal failure, this drug can be used at markedly reduced daily doses and with careful monitoring for anemia. Patients can be started on a low dose of ribavirin, and doses can be increased gradually as long as side effects are manageable [82][83][84] . Only a few reports support the combined use of pegIFN and ribavirin in ESRD patients or patients on HD (Table 1).…”
Section: Combination Therapies: Interferon or Pegifn With Ribavirinmentioning
confidence: 99%
“…Despite the fact that ribavirin is contraindicated in the setting of renal failure, this drug can be used at markedly reduced daily doses and with careful monitoring for anemia. Patients can be started on a low dose of ribavirin, and doses can be increased gradually as long as side effects are manageable [82][83][84] . Only a few reports support the combined use of pegIFN and ribavirin in ESRD patients or patients on HD (Table 1).…”
Section: Combination Therapies: Interferon or Pegifn With Ribavirinmentioning
confidence: 99%
“…134, 135 Liu et al further evaluated PEG-IFN α-2a at a dose of 135 µg per week plus RBV at a dose of 200 mg per day for 48 and 24 weeks in treatment-naïve and -experienced East Asian HCV-1 and HCV-2 patients on hemodialysis. 130,131,136 The SVR rates for treatment-naïve HCV-1 and HCV-2 patients were 64% and 74%, respectively; those for treatment-experienced HCV-1 and HCV-2 patients were 52% and 80%, respectively. Furthermore, Tseng et al evaluated PEG-IFN α-2b at a dose of 1.0 µg per kg of body weight per week plus RBV at a dose of 200 mg three times per week for 48 and 24 weeks in treatment-naïve East Asian HCV-1 and non-HCV-1 patients on hemodialysis, and the overall SVR rate was 62%.…”
mentioning
confidence: 99%
“…[129][130][131] Two recent pilot studies used TVR in combination with PEG-IFN α plus low-dose RBV to treat Western HCV-1 patients on hemodialysis, and the SVR rates were superior to those using PEG-IFN α plus low-dose RBV. 137,138 Whether triple therapy or all oral DAA regimen could benefit Asian patients on hemodialysis deserves further investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 However, several studies reported the use of low-dose ribavirin in combination with interferon, carefully controlling for anemia and monitoring serum concentration of the drug during treatment in hemodialysis patients. [11][12][13] The primary goal of the antivirological treatment is eradication of the HCV infection, which is synonymous with sustained virological response (SVR). The antivirological treatment is prolonged and expensive, complicated by frequent and sometimes serious side effects resulting in treatment discontinuation, and about one-third of the treated hemodialysis patients achieve sustained virological response.…”
Section: Introductionmentioning
confidence: 99%